2020
DOI: 10.5455/aim.2020.28.94-97
|View full text |Cite
|
Sign up to set email alerts
|

Telegram as a Tool to Supplement Online Medical Education During COVID-19 Crisis

Abstract: Introduction: Instant Messaging Applications are known for their potential to enhance learning. However, to date, there has been little investigation into the implications of the ‘Telegram’ application for online medical education and training. Aim: This study explores the potential benefits and disadvantages of integrating Telegram into undergraduate medical education during the COVID-19 pandemic. Methods: An exploratory study was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 17 publications
0
51
0
3
Order By: Relevance
“…Five articles focused on multiple areas and four articles categorized as "other" were diverse and did not clearly fit into another category. Iqbal et al (2020) investigated the use of a free cloud-based App, Telegram, that allowed students to form groups or channels to facilitate sharing of educational resources, communication, collaborative learning, and wellbeing. Students found it effective, but some complained it created overload and caused distraction.…”
Section: Other or Multiple Areas Of Focusmentioning
confidence: 99%
“…Five articles focused on multiple areas and four articles categorized as "other" were diverse and did not clearly fit into another category. Iqbal et al (2020) investigated the use of a free cloud-based App, Telegram, that allowed students to form groups or channels to facilitate sharing of educational resources, communication, collaborative learning, and wellbeing. Students found it effective, but some complained it created overload and caused distraction.…”
Section: Other or Multiple Areas Of Focusmentioning
confidence: 99%
“…Notably, a recent study by Iqbal et al (2020) reported multiple utilities of the app, including easy access to educational resources and the ability to add unlimited members, as well as files in all formats and sizes. In their study with medical students, they found the app assisted students to engage in collaborative learning while maintaining their wellbeing and ensuring their security.…”
Section: Telegram For Teaching and Learningmentioning
confidence: 99%
“…This present study aimed to start the conversation for future studies in other settings, cultures, and universities and thus fill a part of this research gap. Iqbal et al (2020), reported on the use of "Telegram" to support online education for medical students. They found that it brought many advantages, such as positive functionalities in terms of technology.…”
Section: Information Overload and E-learningmentioning
confidence: 99%
“…It also helped students to employ collaborative learning, and sustained student wellbeing, and kept them feeling secure. On the other hand, there were some disadvantages, including IO, and wasted time through distractions (Iqbal et al, 2020). Others have found that IO harmed some students' participation and engagement, but that some students learned to manage it (Chen et al, 2012).…”
Section: Information Overload and E-learningmentioning
confidence: 99%